Predictive Value of Cortical Thickness Measured by Ultrasonography for Renal Impairment: A Longitudinal Study in Chronic Kidney Disease - Hoi, Shotaro (J Clin Med, 2018)
Background: Kidney size is associated with renal function, however it is not elucidated whether kidney size is a risk for the progression of chronic kidney disease. The aim of this study was to investigate the predictive value of morphological evaluation of kidney size by ultrasonography for the progression of renal dysfunction. Methods: Morphological parameters including kidney length, volume, cortical thickness, and medullary thickness were measured by ultrasonography in 87 patients with chronic kidney disease, and adjusted by body size. Renal functions at baseline and after 2 years were measured and the associations of morphological parameters to decline in renal function over 2 years were analyzed. Results: Height-adjusted cortical thickness was correlated to decline in renal function (r = 0.426, p < 0.001). Height-adjusted cortical thickness could predict renal dysfunction with the area under the curve of 0.786, and height-adjusted cortical thickness of 4.0 mm/cm was a cut off value with a sensitivity of 72.5% and a specificity of 80.0% for the risk of a more than 30% decline in renal function or initiation of dialysis. Conclusions: We provide new insights into the utility of measuring cortical thickness by ultrasonography for predict future renal impairment.